The Columbia companion to American history on film how the movies have portrayed the American past - Rollins, Peter C.; Gale Group (New York Columbia University Press, 2003)
Collection of essays that explore how major eras, institutions, peoples, wars, leaders, social groups, and myths of our national culture have been portrayed on film.
Acknowledgments -- Introduction -- I. Eras -- II. Wars and other major events -- III. Notable people -- IV. Groups -- V. Institutions and movements -- VI. Places -- VII. Themes and topics -- VIII. Myths and heroes -- Index.
Electronic reproduction.
Keywords: Historical films -- United States; Electronic books; United States -- In motion pictures; United States -- History -- Miscellanea